Early detection of left fallopian tube carcinosarcoma by transvaginal sonography: a case report and review of diagnostic challenges - Chang, Junjie; Zhang, Wenjun; Wang, Hua; Song, Xin; Yu, Dan (Frontiers in Oncology, 2025)
Fallopian tube carcinosarcoma (FTCS) is an extremely rare and aggressive malignancy, its nonspecific clinical presentation and anatomical location make preoperative diagnosis challenging, often lead to delayed treatment and poor outcomes. Here, we present a case of early-stage FTCS in a 57-year-old postmenopausal woman who presented with vaginal bleeding. Transvaginal sonography (TVS) played a pivotal role in identifying a characteristic sausage-shaped adnexal mass, which was missed on enhanced computed tomography (ECT). The patient underwent comprehensive surgical staging, including total hysterectomy and bilateral adnexectomy, with pathology confirming FTCS, FIGO stage IA. Immunohistochemical analysis revealed a biphasic tumor with strong P53 positivity and a high Ki-67 index (80%), indicative of its aggressive nature. Despite declining adjuvant therapy beyond two cycles of chemotherapy, the patient remained recurrence-free at 24 months postoperatively. This case highlights the critical role of TVS in the early detection of FTCS and underscores the importance of timely surgical intervention in improving outcomes. We also discuss the diagnostic challenges, pathological features, and therapeutic considerations of FTCS, emphasizing the need for further research to optimize diagnostic and treatment strategies for this rare malignancy.